Sri Lankan Population Change and Demographic Bonus Challenges and Opportunities in the New Millennium - de Silva, W. Indralal (My University, 2012)
This paper examines the population changes and the related causative factors, namely fertility, mortality and international migration in Sri Lanka. During the past decades, the total size, as well as the age and sex structure of the population, was exposed to irreversible changes. The age structure transition has produced a demographic bonus conducive for an economic takeoff. During this period, the proportion of people of working age (15-59) is larger than the fraction in the dependent age categories. The paper includes a sector analysis of the employed population in the agriculture, industry and service sectors to identify the growth sectors of the economy and to reveal the potential patterns and levels of utilization of the demographic bonus. Finally, the social safety net implications of the emerging population, such as the dependency burden, aging, disability and the disintegration of traditional family system in Sri Lanka are examined. Sri Lanka's population has grown to 20 million in 2010, an almost eight-fold increase since the census of 1871. The population doubled 54 years after the first census (1925), then again in 35 years (1960), as a result of the relatively high population growth rate. The 2001 census calculated a population 18.7 million. By 2003, the population was estimated to be 19.2 million, a third doubling in 43 years. By 2010, the population of Sri Lanka had passed the 20 million mark
Keywords: Sri Lankan Population Change and Demographic Bonus Challenges and Opportunities in the New Millennium